Whisker oriented toughened white silicon nitride ceramic and method of making same
Patent Information
- Application Number
- CN202410357259.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-27
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-03-27
AI Technical Summary
[0005]本发明的目的之二是提供上述制备方法制得的晶须定向增韧白色氮化硅陶瓷,解决氮化硅陶瓷力学性能和外观匹配性差的问题
[0019] 1. This invention selects boron nitride whiskers as the toughening material. These are fibrous one-dimensional materials composed of nitrogen and boron atoms, possessing a single-crystal structure, highly ordered atomic arrangement, and low defect rate, effectively improving the fracture toughness and oxidation resistance of silicon nitride ceramics. A powder lamination process is employed to orient the whiskers within the dry-pressed preform, achieving directional toughening. Compared to the layer-by-layer assembly method of tape casting, this avoids problems such as low preform density due to low solid content in tape castings, and unstable material properties and uneven color caused by high carbon content due to organic residues.
Smart Images

Figure CN118146006B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic material preparation technology, specifically to a whisker-oriented toughened white silicon nitride ceramic and its preparation method. Background Technology
[0002] Silicon nitride ceramics are non-oxide ceramic materials with excellent mechanical and physical properties, widely used in engineering structures, machinery manufacturing, and electronic information fields. Their unique biocompatibility extends their application to the biomedical field, making them one of the most promising ceramic materials in the modern cutting-edge technology materials family. However, despite the high strength, high hardness, excellent wear resistance, acid and alkali resistance, and non-cytotoxicity of dense silicon nitride ceramics, they are also brittle and have low toughness, making them highly susceptible to breakage from external impacts. Furthermore, their grayish-black appearance significantly limits their application in dental restorations, smart mobile device casings, and other fields. Therefore, achieving a balance between strength, toughness, and appearance in dense silicon nitride ceramics is a pressing issue that needs to be addressed.
[0003] To address the aforementioned issues, Chinese patent application CN115353400A discloses a toughened silicon nitride ceramic material and its preparation method. Using modified carbon nanotubes with good toughness as the modifier, the toughened silicon nitride ceramic material is prepared using a vacuum hot pressing process. This method can effectively improve the fracture toughness of silicon nitride ceramics while ensuring high flexural strength. However, on the one hand, the vacuum hot pressing process has high energy consumption and low production volume, making it difficult to industrialize; on the other hand, the addition of carbon nanotubes exacerbates the gray-black color of the silicon nitride ceramic. Chinese patent application CN114853482A discloses a high-toughness silicon nitride nanowire / silicon nitride layered ceramic and its preparation method. Using silicon nitride nanowire paper as the soft phase and silicon nitride ceramic as the hard phase, the layers are stacked in a layer-by-layer assembly manner and then hot-pressed to prepare the toughened silicon nitride layered ceramic. Although this method effectively improves the fracture toughness of silicon nitride ceramics, its flexural strength is only 300 MPa, and the appearance of the material is not described. Chinese patent application CN110818428A discloses a method for preparing eutectic reinforced and toughened silicon nitride ceramics. This method uses discharge plasma sintering and gas pressure sintering processes to form a eutectic structure of α and β phases in silicon nitride material, thereby obtaining a silicon nitride reinforced and toughened ceramic. Although this method can effectively improve the strength and toughness of silicon nitride ceramics, the process is complex, the application range of special products is narrow, and the appearance problem of ceramic materials is not solved. Summary of the Invention
[0004] One of the objectives of this invention is to provide a method for preparing whisker-oriented toughened white silicon nitride ceramics, which is simple in process, low in energy consumption, easy to process into complex shapes and has a white appearance, and is suitable for the industrial production of products that require mechanical properties and appearance.
[0005] The second objective of this invention is to provide a whisker-oriented toughened white silicon nitride ceramic prepared by the above-mentioned method, thereby solving the problem of poor matching between the mechanical properties and appearance of silicon nitride ceramics.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0007] In a first aspect, the present invention provides a method for preparing whisker-oriented toughened white silicon nitride ceramic, comprising the following steps:
[0008] S1: Using α-silicon nitride as raw material, yttrium oxide, magnesium oxide and silicon oxide as additives, and zirconium oxide balls and anhydrous ethanol as ball milling media, the mixture is placed in a polytetrafluoroethylene can for ball milling, dried, and then passed through a 100-mesh sieve to obtain a white mixed powder.
[0009] S2: The white mixed powder and boron nitride whiskers obtained in step S1 are loaded into a self-made stainless steel mold using a stacking process. The molded blank is then obtained by dry pressing using uniaxial pressure. Finally, the blank is obtained by cold isostatic pressing.
[0010] S3: Place the shaped blank obtained in step S2 into a boron nitride crucible and fill and cover it with boron nitride powder. Place the boron nitride crucible in a vacuum furnace with inert gas protection for the first step of low-temperature pressureless sintering. After cooling, a whisker-oriented toughened white silicon nitride ceramic block that can be easily processed is obtained. After processing into the target shape, place it into a boron nitride crucible and fill and cover it with boron nitride powder. Place the boron nitride crucible in a vacuum furnace with inert gas protection for the second step of high-temperature pressureless sintering. After cooling, the target product is obtained.
[0011] Preferably, in step S1, the amount of additive added is 7% to 11% of the mass of α-silicon nitride, the mass ratio of raw material additive mixed powder, zirconia balls, and anhydrous ethanol is 1:1:1.2, the ball milling time is 8 to 12 hours, the ball milling speed is 180 to 220 rpm, and the drying temperature is 60 to 80°C.
[0012] More preferably, the amount of yttrium oxide added is 2% to 3%, the amount of magnesium oxide added is 2% to 3%, and the amount of silicon oxide added is 3% to 5%.
[0013] Preferably, in step S2, the thickness ratio of the white mixed powder to the boron nitride whiskers is controlled to be 3:1 to 5:1, the dry pressing pressure is 25 to 35 MPa, and the cold isostatic pressing pressure is 280 to 320 MPa.
[0014] Preferably, in step S3, the first low-temperature pressureless sintering temperature is 1000-1200℃ and the holding time is 1-3h; the second low-temperature pressureless sintering temperature is 1350-1450℃ and the holding time is 1-3h.
[0015] Preferably, the inert gas in step S3 is nitrogen or argon.
[0016] Secondly, the present invention provides a whisker-oriented toughened white silicon nitride ceramic prepared by the above-described preparation method.
[0017] The preparation method of this invention uses a powder stacking process to directionally arrange whiskers in a dry-pressed blank to achieve directional toughening. After cold isostatic pressing, a shaped blank is obtained. The blank is then placed in a vacuum furnace for low-temperature sintering and annealing to obtain an easily processed whisker-oriented toughened white silicon nitride ceramic block. After high-temperature sintering and annealing, the target product is obtained. This method achieves low-energy and high-efficiency preparation of products that combine mechanical properties and white appearance, and is suitable for the industrial production of products that require both mechanical properties and appearance.
[0018] Compared with the prior art, the beneficial effects of the present invention are:
[0019] 1. This invention selects boron nitride whiskers as the toughening material. These are fibrous one-dimensional materials composed of nitrogen and boron atoms, possessing a single-crystal structure, highly ordered atomic arrangement, and low defect rate, effectively improving the fracture toughness and oxidation resistance of silicon nitride ceramics. A powder lamination process is employed to orient the whiskers within the dry-pressed preform, achieving directional toughening. Compared to the layer-by-layer assembly method of tape casting, this avoids problems such as low preform density due to low solid content in tape castings, and unstable material properties and uneven color caused by high carbon content due to organic residues.
[0020] 2. The present invention uses boron nitride powder to fill the boron nitride crucible, which can protect the silicon nitride ceramic from being contaminated by the carbon tube of the vacuum furnace on the one hand, and further protect the silicon nitride ceramic from being oxidized by residual oxygen on the other hand. At the same time, the boron nitride powder can be recycled and reused multiple times.
[0021] 3. The toughened silicon nitride ceramics prepared by this method have a sintering temperature that is about 200℃ lower than that of hot pressing or gas pressure sintering processes. The crystal size is small and uniform. The process is simple, energy consumption and cost are low, and it is suitable for the industrial production of products that require mechanical properties and appearance. Attached Figure Description
[0022] To more clearly illustrate the technical solutions of the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0023] Figure 1 The XRD pattern of the whisker-oriented toughened white silicon nitride ceramic in Example 2;
[0024] Figure 2 Optical photographs of the actual samples at each stage in Example 2;
[0025] Figure 3 This is a SEM image of the white silicon nitride ceramic surface after HF acid etching in Example 2, showing the directionally toughened whisker pattern. Detailed Implementation
[0026] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0027] The raw material powders used in the following examples are all commercially available products with a purity greater than 99.9%.
[0028] Example 1
[0029] S1: Using 100 parts of α-silicon nitride as raw material, add 2 parts of yttrium oxide, 2 parts of magnesium oxide and 3 parts of silicon oxide as additives, use 100 parts of zirconia balls and 120 parts of anhydrous ethanol as ball milling media, put it into a polytetrafluoroethylene can and ball mill at 180 rpm for 8 hours, dry at 60℃, and pass through a 100-mesh sieve to obtain a white mixed powder;
[0030] S2: The white mixed powder and boron nitride whiskers obtained in step S1 are loaded into a self-made stainless steel mold using a stacking process. The thickness ratio of the mixed powder to the boron nitride whiskers is 3:1. A dry-pressed blank is obtained by applying 25MPa uniaxial pressure and holding the pressure for 60s. A shaped blank is obtained by applying 280MPa cold isostatic pressing and holding the pressure for 180s.
[0031] S3: Place the shaped blank obtained in step S2 into a boron nitride crucible and fill and cover it with boron nitride powder. Place the boron nitride crucible in a vacuum furnace under nitrogen protection and sinter at a low temperature of 1000℃ for 1 hour. After cooling, process the toughened white silicon nitride ceramic in terms of size and shape. Place the processed silicon nitride ceramic into a boron nitride crucible and fill and cover it with boron nitride powder. Place the boron nitride crucible in a vacuum furnace under nitrogen protection and sinter at a low temperature of 1350℃ for 1 hour. After cooling, obtain the target product.
[0032] Example 2
[0033] S1: Using 100 parts of α-silicon nitride as raw material, add 2 parts of yttrium oxide, 2 parts of magnesium oxide and 5 parts of silicon oxide as additives, use 100 parts of zirconia balls and 120 parts of anhydrous ethanol as ball milling media, put them into a polytetrafluoroethylene can and ball mill at 200 rpm for 8 hours, dry at 60℃, and pass through a 100-mesh sieve to obtain a white mixed powder;
[0034] S2: The white mixed powder and boron nitride whiskers obtained in step S1 are loaded into a self-made stainless steel mold using a stacking process. The thickness ratio of the mixed powder to the boron nitride whiskers is 5:1. A dry-pressed blank is obtained by applying 25MPa uniaxial pressure and holding the pressure for 60s. A shaped blank is obtained by applying 280MPa cold isostatic pressing and holding the pressure for 180s.
[0035] S3: Place the shaped blank obtained in step S2 into a boron nitride crucible and fill and cover it with boron nitride powder. Place the boron nitride crucible in a vacuum furnace under nitrogen protection and sinter at 1200℃ for 2 hours without pressure. After cooling, process the toughened white silicon nitride ceramic to the required dimensions and shape. Place the processed silicon nitride ceramic into a boron nitride crucible and fill and cover it with boron nitride powder. Place the boron nitride crucible in a vacuum furnace under nitrogen protection and sinter at 1450℃ for 2 hours without pressure. After cooling, the target product is obtained. Figure 1 XRD pattern of whisker-oriented toughened white silicon nitride ceramic. Figure 2 Optical photographs of the actual samples at each stage. Figure 3 This is a SEM image of a white silicon nitride ceramic surface with whisker-oriented toughening after HF acid etching.
[0036] Example 3
[0037] S1: Using 100 parts of α-silicon nitride as raw material, add 3 parts of yttrium oxide, 3 parts of magnesium oxide and 5 parts of silicon oxide as additives, use 100 parts of zirconia balls and 120 parts of anhydrous ethanol as ball milling media, put it into a polytetrafluoroethylene can and ball mill at 200 rpm for 8 hours, dry at 60℃, and pass through a 100-mesh sieve to obtain a white mixed powder;
[0038] S2: The white mixed powder and boron nitride whiskers obtained in step S1 are loaded into a self-made stainless steel mold using a stacking process. The thickness ratio of the mixed powder to the boron nitride whiskers is 5:1. A dry-pressed blank is obtained by applying 35MPa uniaxial pressure and holding the pressure for 60s. A shaped blank is obtained by applying 320MPa cold isostatic pressing and holding the pressure for 180s.
[0039] S3: Place the shaped blank obtained in step S2 into a boron nitride crucible and fill and cover it with boron nitride powder. Place the boron nitride crucible in a vacuum furnace under nitrogen protection and sinter at a low temperature of 1200℃ for 3 hours. After cooling, process the toughened white silicon nitride ceramic in terms of size and shape. Place the processed silicon nitride ceramic into a boron nitride crucible and fill and cover it with boron nitride powder. Place the boron nitride crucible in a vacuum furnace under nitrogen protection and sinter at a low temperature of 1350℃ for 3 hours. After cooling, obtain the target product.
[0040] Comparative Example 1 (The difference between Comparative Example 1 and Example 1 is that boron nitride whiskers are not added as a toughening material in step S2)
[0041] S1: Using 100 parts of α-silicon nitride as raw material, add 2 parts of yttrium oxide, 2 parts of magnesium oxide and 3 parts of silicon oxide as additives, use 100 parts of zirconia balls and 120 parts of anhydrous ethanol as ball milling media, put it into a polytetrafluoroethylene can and ball mill at 180 rpm for 8 hours, dry at 60℃, and pass through a 100-mesh sieve to obtain a white mixed powder;
[0042] S2: The white mixed powder obtained in step S1 is loaded into a self-made stainless steel mold, and a dry-pressed blank is obtained by applying a uniaxial pressure of 25MPa and holding the pressure for 60s. A shaped blank is obtained by applying a cold isostatic pressing of 280MPa and holding the pressure for 180s.
[0043] S3: Place the shaped blank obtained in step S2 into a boron nitride crucible and fill and cover it with boron nitride powder. Place the boron nitride crucible in a vacuum furnace under nitrogen protection and sinter at a low temperature of 1000℃ for 1 hour. After cooling, process the toughened white silicon nitride ceramic in terms of size and shape. Place the processed silicon nitride ceramic into a boron nitride crucible and fill and cover it with boron nitride powder. Place the boron nitride crucible in a vacuum furnace under nitrogen protection and sinter at a low temperature of 1350℃ for 1 hour. After cooling, obtain the target product.
[0044] Comparative Example 2 (The difference between Comparative Example 2 and Example 2 is that the dry-pressed green blank is not subjected to cold isostatic pressing in step S2)
[0045] S1: Using 100 parts of α-silicon nitride as raw material, add 2 parts of yttrium oxide, 2 parts of magnesium oxide and 5 parts of silicon oxide as additives, use 100 parts of zirconia balls and 120 parts of anhydrous ethanol as ball milling media, put them into a polytetrafluoroethylene can and ball mill at 200 rpm for 8 hours, dry at 60℃, and pass through a 100-mesh sieve to obtain a white mixed powder;
[0046] S2: The white mixed powder and boron nitride whiskers obtained in step S1 are loaded into a self-made stainless steel mold using a stacking process. The thickness ratio of the mixed powder to the boron nitride whiskers is 5:1. A dry-pressed blank is obtained by applying a uniaxial pressure of 25MPa and holding the pressure for 60s.
[0047] S3: Place the dry-pressed green blank obtained in step S2 into a boron nitride crucible and fill and cover it with boron nitride powder. Place the boron nitride crucible in a vacuum furnace under nitrogen protection and sinter at a low temperature of 1200℃ for 2 hours. After cooling, process the toughened white silicon nitride ceramic in terms of size and shape. Place the processed silicon nitride ceramic into a boron nitride crucible and fill and cover it with boron nitride powder. Place the boron nitride crucible in a vacuum furnace under nitrogen protection and sinter at a low temperature of 1450℃ for 2 hours. After cooling, obtain the target product.
[0048] Comparative Example 3 (The difference between Comparative Example 3 and Example 2 is that boron nitride powder is not used for filling in step S3 of the green blank)
[0049] S1: Using 100 parts of α-silicon nitride as raw material, add 2 parts of yttrium oxide, 2 parts of magnesium oxide and 5 parts of silicon oxide as additives, use 100 parts of zirconia balls and 120 parts of anhydrous ethanol as ball milling media, put them into a polytetrafluoroethylene can and ball mill at 200 rpm for 8 hours, dry at 60℃, and pass through a 100-mesh sieve to obtain a white mixed powder;
[0050] S2: The white mixed powder and boron nitride whiskers obtained in step S1 are loaded into a self-made stainless steel mold using a stacking process. The thickness ratio of the mixed powder to the boron nitride whiskers is 5:1. A dry-pressed blank is obtained by applying 25MPa uniaxial pressure and holding the pressure for 60s. A shaped blank is obtained by applying 280MPa cold isostatic pressing and holding the pressure for 180s.
[0051] S3: Place the shaped blank obtained in step S2 into a boron nitride crucible, place the boron nitride crucible in a vacuum furnace under nitrogen protection, and perform low-temperature pressureless sintering at 1200℃ for 2 hours. After cooling, process the toughened white silicon nitride ceramic in terms of size and shape. Place the processed silicon nitride ceramic into a boron nitride crucible, place the boron nitride crucible in a vacuum furnace under nitrogen protection, and perform low-temperature pressureless sintering at 1450℃ for 2 hours. After cooling, obtain the target product.
[0052] The test results of silicon nitride ceramics obtained in Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1. The number of samples used for the flexural strength and fracture toughness tests was 10 each.
[0053] Table 1
[0054] Example 1 1027±12 12.7±0.5 White and uniform Example 2 1215±8 14.4±0.3 White and uniform Example 3 1233±11 14.2±0.5 White and uniform Comparative Example 1 1122±9 6.7±0.3 White and uniform Comparative Example 2 839±7 8.5±0.3 White and uniform Comparative Example 3 983±6 10.4±0.7 dotted gray-black
[0055] The test results in Table 1 show that boron nitride whiskers can significantly improve the fracture toughness of silicon nitride ceramics. This is because boron nitride whiskers have a high aspect ratio and a regular morphology, allowing them to effectively disperse and orient themselves within silicon nitride ceramics to bear loads. The cold isostatic pressing process can further improve the density of the formed green body, effectively enhancing the flexural strength and fracture toughness of zirconia ceramics. The inclusion of boron nitride powder can effectively prevent the infiltration of carbon elements in the vacuum furnace, protecting silicon nitride ceramics from carbon contamination and ensuring their color uniformity.
Claims
1. A method for preparing whisker-oriented toughened white silicon nitride ceramic, characterized in that, Includes the following steps: S1: Using α-silicon nitride as raw material, yttrium oxide, magnesium oxide and silicon oxide as additives, and zirconium oxide balls and anhydrous ethanol as ball milling media, the mixture is placed in a polytetrafluoroethylene can for ball milling, dried, and then passed through a 100-mesh sieve to obtain a white mixed powder. S2: The white mixed powder and boron nitride whiskers obtained in step S1 are loaded into a self-made stainless steel mold using a stacking process. The mold is then dry-pressed using uniaxial pressure to obtain a dry-pressed blank, and then cold isostatic pressing is used to obtain a shaped blank. The thickness ratio of the white mixed powder to the boron nitride whiskers is controlled to be 3:1 to 5:1 in the stacking process, the dry pressing pressure is 25 to 35 MPa, and the cold isostatic pressing pressure is 280 to 320 MPa. S3: Place the shaped blank obtained in step S2 into a boron nitride crucible and fill and cover it with boron nitride powder. Place the boron nitride crucible in a vacuum furnace under inert gas protection for the first step of low-temperature pressureless sintering. After cooling, an easily machinable whisker-oriented toughened white silicon nitride ceramic block is obtained. After being processed into the target shape, it is placed in a boron nitride crucible and filled and covered with boron nitride powder. Place the boron nitride crucible in a vacuum furnace under inert gas protection for the second step of high-temperature pressureless sintering. After cooling, the target product is obtained. The temperature of the first step of low-temperature pressureless sintering is 1000~1200 ℃, and the holding time is 1~3 h. The temperature of the second step of high-temperature pressureless sintering is 1350~1450 ℃, and the holding time is 1~3 h.
2. The method for preparing whisker-oriented toughened white silicon nitride ceramic according to claim 1, characterized in that, In step S1, the amount of additive added is 7% to 11% of the mass of α-silicon nitride, the mass ratio of raw material additive mixed powder, zirconia balls, and anhydrous ethanol is 1:1:1.2, the ball milling time is 8 to 12 h, the ball milling speed is 180 to 220 rpm, and the drying temperature is 60 to 80 ℃.
3. The method for preparing whisker-oriented toughened white silicon nitride ceramic according to claim 2, characterized in that, The amount of yttrium oxide added is 2%~3%, the amount of magnesium oxide added is 2%~3%, and the amount of silicon oxide added is 3%~5%.
4. The method for preparing whisker-oriented toughened white silicon nitride ceramic according to claim 1, characterized in that, In step S3, the inert gas is either nitrogen or argon.
5. Whisker-oriented toughened white silicon nitride ceramic prepared by the preparation method according to any one of claims 1 to 4.
Citation Information
Patent Citations
Preparation method of eutectic, reinforced and toughened silicon nitride ceramic
CN110818428A
Toughened silicon nitride ceramic material and preparation method thereof
CN115353400A
Method for toughening silicon nitride ceramic with boron nitride nanotubes and product prepared with method
CN108298996A
High-toughness silicon nitride nanowire / silicon nitride layered ceramic and preparation method thereof
CN114853482A
Preparation method of silicon nitride ceramic with high thermal conductivity and low resistivity
CN116217239A